Case report: Conquer a complex variant: Coronary-pulmonary artery fistulas, atrial septal defect and bicuspid pulmonary valve, under beating heart surgery - Zhou, Ting; Liu, Chaobing; Zhang, Songlin (Frontiers in Cardiovascular Medicine, 2022)
Coronary artery to pulmonary artery fistula(CPAF) is a congenital or acquired abnormal channel between arteries, with a left- to- right cardiac shunting, which may lead to myocardial ischemia, arrhythmia, thrombotic complications and heart failure. CPAF is usually detected by coronary angiography, and few reports have used beating heart surgery as detection method. A 39–year-old male diagnosed with atrial septal defect (ASD), bicuspid pulmonary valve, and moderate tricuspid regurgitation, and he is totally asymptomatic. In preoperative evaluation, significant CPAF was suspected by echocardiography. The patient refused to conduct coronary angiography due to allergic history. Therefore, the cardiac team designed and deployed the use of on pump beating heart surgery to detect and repair these disorders, and suggested that OPBHS as myocardial protection strategy for patient at low surgical risk. The rare and complex cardiovascular case that CPAFs from two branches of the left anterior descending coronary artery to the main pulmonary artery with ASD ,bicuspid pulmonary valve ,and moderate tricuspid regurgitation has not yet been reported in the literature, and its embryological hypothesis has been further analyzed.